PENGARUH LITERASI KEUANGAN DAN RETURN INVESTASI TERHADAP MINAT BERINVESTASI SAHAM DENGAN INFLUENCER MEDIA SOSIAL SEBAGAI VARIABEL MODERASI PADA GENERASI Z - Linda Purba Ningrum; Kurnia Rina Ariani (JURNAL LENTERA BISNIS, 2026)
This scholarly investigation seeks to examine the influence of financial literacy and stock investment returns, with social media influencers serving as moderating variables within Generation Z. Employing a quantitative research design, primary data was gathered through the dissemination of questionnaires directed at students from the Faculty of Economics and Business at the University of Muhammadiyah Surakarta during the timeframe of 2022 to 2024. Objective sampling techniques were implemented, encompassing a sample of 114 undergraduate participants. Analytical approaches utilized include assessments of validity, evaluations of reliability, classical assumption testing, in addition to Moderated Regression Analysis (MRA). The results indicated that both investment returns and social media influencers significantly impacted interest in stock investments, while financial literacy did not have a noteworthy effect on this interest. Furthermore, social media influencers did not moderate the association between financial literacy and investment interest but were effective in moderating the connection between investment returns and investment interest, consequently diminishing the strength of that relationship. This research underscores the significant role of digital elements, particularly social media influencers, in shaping Generation Z's investment behaviors within the modern digital environment.